Peranan Pengobatan dengan Akupuntur pada Diabetes Mellitus dalam Era Globalisasi - Dewi, Kartika (Zenit, 2012)
In the globalization era, acupuncture can be used as a  treatment for several medication when purposeswestern medicine is not effective enough or contraindicated. Recently acupuncture has been used world wide, including in Indonesia. Diabetes Mellitus is a chronic disturbance of carbohydrate metabolism due to less production or  utilization of insulin, with  symptoms like hyperglycemia, glucosuria, polyphagia, polydipsia and polyuria. In Traditional Chinese Medicine, Diabetes Mellitus is known as Xiao Ke. It is a condition when San Jiao  is attacked by inner heat and the result is body fuid imbalance. Acute complication is ketoacidosis,  while chronic complications are usually nephropathy, retinopathy, polyneuropathy and cardiovascular diseases. Oral hypoglycemic agents or insulin are usually given for the treatment, while diet and exercise must also be done properly. Acupuncture can  also be chosen as an alternative/complementary treatment and the result is effective and without side effects.Keywords: diabetes mellitus, acupuncture